Transformando saberes e práticas: trilhos e trilhas da educação permanente para agentes comunitários e de combate às endemias da Atenção Primária à Saúde - Rios, Thays Santos (2025)
The change in the health services scenario following the 1980 Health Reform demanded transformations in the performance of health workers, whose training was the responsibility of the Unified Health System (SUS) model. Included in this is the APS, which is responsible for comprehensive and longitudinal care in the SUS care network. Thus, Permanent Education in Health (EPS) emerged, which, given its importance, soon became a National Policy for Permanent Education in Health (PNEPS), being defined as learning based on problematization in the workplace. Corroborating this idea and supported by the PNEPS, the Health with Agent Program (PSA) was established. This Program, currently called “More Health with Agents” (PSA), aims to provide technical training for Community Health Agents (ACS) and Endemic Disease Control Agents (ACE) who work throughout the country. In view of this, it becomes extremely important to analyze the development of their actions in the territories of execution, which is the general objective of this study. To this end, it presented specific objectives to understand the perception of the actors involved; describe the pedagogical methodologies used; identify the transformations that occurred in the work process and understand the advantages and disadvantages of developing the course activities. This is a descriptive qualitative research. Documentary research and semi-structured interviews were used as data collection instruments, analyzed using Bardin's content analysis technique, with data triangulation and the help of WebQDA software. The research participants were the ACS, ACE, supervisors, tutors, preceptors and managers linked to the PSA and the municipality of Itaberaba-BA, the location of the study. In total, 26 workers participated in the study. The categories were constructed according to interpretations and critical reflections. Regarding the actors’ perception of the PSA, the course was perceived positively. The following were identified as being subject to improvement: monitoring of field practices; number of students per class; delivery time of material resources for practices; the workload allocated to preceptorship activities; the lack of institutional support; the distribution of program content. The relationship with Information and Communication Technologies (ICTs) was the most mentioned difficulty. Parallel to this was the difficulty participants had in reconciling personal, course and work responsibilities. The lack of ACS and ACE integration in the municipality was also an important point of emphasis in the development of activities. On the other hand, the teaching materials were very well evaluated. Finally, changes in the students’ work process were analyzed in light of micropolitics. The PSA strengthened the identity of professionals, highlighting their importance within the SUS. This, in addition to being converted into the quality of their work, also generated feelings of professional satisfaction and motivation to carry out their duties. Based on the results of this research, it is expected to contribute to the improvement of the PSA in the city of ItaberabaBA or in other similar contexts, as well as to strengthen the development of EPS actions from the municipality's APS. To assist in this process, a PSA implementation guide for municipal managers was created as a technical product, based on the main findings and an intervention project.